2017
DOI: 10.15252/emmm.201708194
|View full text |Cite
|
Sign up to set email alerts
|

Thwarting endogenous stress: BRCA protects against aldehyde toxicity

Abstract: Homologous recombination (HR) and the Fanconi Anemia (FA) pathways constitute essential repair pathways for DNA damage, which includes DNA double‐stranded breaks (DSB) and inter‐strand cross‐links (ICL), respectively. Germline mutations affecting a single copy of the HR factors BRCA1 and BRCA2 predispose individuals to cancers of the breast, ovary, prostate, and pancreas. Cells deficient for BRCA proteins display high levels of genome instability due to defective repair of endogenous DSBs and are also exquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Dysfunction of BRCA1/2 leads to cancer susceptibility via the induction of chromosomal instability and mutagenesis [32,33]. Several studies have shown that environmental and endogenous toxins, such as aldehydes, induce genomic instability, and BRCA1 and/or BRCA2 protect against such toxicity and suppress tumorigenesis [34][35][36]. In addition, endogenous acetaldehyde toxicity may induce BRCA2 haploinsufficiency [35].…”
Section: • Hr Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of BRCA1/2 leads to cancer susceptibility via the induction of chromosomal instability and mutagenesis [32,33]. Several studies have shown that environmental and endogenous toxins, such as aldehydes, induce genomic instability, and BRCA1 and/or BRCA2 protect against such toxicity and suppress tumorigenesis [34][35][36]. In addition, endogenous acetaldehyde toxicity may induce BRCA2 haploinsufficiency [35].…”
Section: • Hr Repairmentioning
confidence: 99%
“…In addition, endogenous acetaldehyde toxicity may induce BRCA2 haploinsufficiency [35]. According to such reports, aldehyde accumulation may modulate tissue-specific cancer progression in BRCA1/2 GPV carriers, with implications for public health [34] • DNA Damage-induced Cell Cycle Checkpoints…”
Section: • Hr Repairmentioning
confidence: 99%
“…This observation, originally demonstrated on murine models, was clinically corroborated by the discovery of a higher prevalence of bone-marrow failure in patients affected by Fanconi anemia harboring also a dominant negative polymorphism in the ALDH2 gene which is frequent in the Asian population [ 129 ]. Moreover, the expression BRCA1 and BRCA2 tumor suppressors genes, known to contribute to DNA repair [ 130 ], has been associated to a protective role against endogenous acetaldehyde toxicity [ 131 ]. Consequently, endogenous aldehydes may be implicated in triggering carcinogenesis in BRCA2 mutation carriers [ 132 ].…”
Section: Alcohol Toxicity On Stem Cells: In Search For Molecular Mechmentioning
confidence: 99%